1860 Ga. Laws 56 - (:unkn) unknown (My University, 1860)
No. 63, § 1: Prohibited the sale or furnishing of any gun, pistol, Bowie knife, slungshot, sword cane, or other weapon to a "slave or free person of color." Punishable by fine up to $500 and imprisonment up to 6 months.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES